The roles of competition on innovation efficiency and firm performance: Evidence from the Chinese manufacturing industry - Xunjiang Huang (European Research on Management and Business Economics (ERMBE), 2023)
Firms, especially Chinese manufacturing firms, invest significant resources in innovation activities to sustain their position in the intensifying competitive environment. However, innovation efficiency has led to growing concerns due to the rapid increase in R&D expenditures. The purpose of this study is to explore the complicated role of competition on innovation efficiency and firm performance with a sample of 12,020 Chinese manufacturing firms for the period 2005-2007. The results show that most Chinese manufacturing firms are inefficient in R&D activities. Competition forces firms to focus on the improvement of innovation efficiency, but at the same time, it also undermines collaboration and leads to unpredictable R&D results. Therefore, there is an inverted U-shaped relationship between these variables. Competition also negatively moderates the positive impact of innovation efficiency on firm performance. The findings help firms formulate appropriate innovation strategies for sustainable innovation performance.
Keywords: O32; L11; L60; 650; Competition; Innovation efficiency; Firm performance; Sustainable innovation